Review: A silent concert in developing plants: Dynamic assembly of cullin-RING ubiquitin ligases. (May 2023) - Li, Lihong; Wang, Kankan; Zhou, Yun; Liu, Xing
Abstract: Plants appear quiet: quietly, they break the ground, expand leaves, search for resources, alert each other to invaders, and heal their own wounds. In contrast to the stationary appearance, the inside world of a plant is full of movements: cells divide to increase the body mass and form new organs; signaling molecules migrate among cells and tissues to drive transcriptional cascades and developmental programs; macromolecules, such as RNAs and proteins, collaborate with different partners to maintain optimal organismal function under changing cellular and environmental conditions. All these activities require a dynamic yet appropriately controlled molecular network in plant cells. In this short review, we used the regulation of cullin-RING ubiquitin ligases (CRLs) as an example to discuss how dynamic biochemical processes contribute to plant development. CRLs comprise a large family of modular multi-unit enzymes that determine the activity and stability of diverse regulatory proteins playing crucial roles in plant growth and development. The mechanism governing the dynamic assembly of CRLs is essential for CRL activity and biological function, and it may provide insights and implications for the regulation of other dynamic multi-unit complexes involved in fundamental processes such as transcription, translation, and protein sorting in plants. Highlights: Controlled yet flexible molecular networks drive optimal plant growth and development. Cells maintain a dynamic repertoire of cullin-RING ubiquitin ligases (CRLs). Adaptive assembly of CRLs sustains molecular and developmental plasticity.